Value-at-Risk for Financial Derivative Instruments - Lv, Mingyue (2011)
With the continuous development of the financial industry, financial risk management is increasingly important, the use of scientific methods to do the risk measure also gradually become a hot field. In this paper, quantitative risk analysis method which is widely recognized by the financial industry is introduced. It is called Value-at-Risk (VaR). Value-at-Risk is one of the most popular ways to estimate risk of financial instruments. Abundant previous work focused on linear portfolio. The researches on nonlinear portfolio are rare. The linear approximations, such as delta-only model or variance-covariance method, will underestimate or overestimate VaR for nonlinear financial instruments or portfolios. This paper aims to examine characteristics of VaR for nonlinear portfolios. Thus, three classic methods which can be applied for nonlinear portfolio have been selected, historical simulation model, quadratic model, and Monte Carlo simulation model. Owing to this article includes introduction about various aspects of VaR models on nonlinear type of derivative instruments, it may be treated as an introduction about this particular field of financial research.